2022
DOI: 10.18632/aging.204461
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane postconditioning ameliorates cerebral ischemia-reperfusion injury in rats via TLR4/MyD88/TRAF6 signaling pathway

Abstract: To determine whether sevoflurane postconditioning protects against cerebral ischemia reperfusion (I/R) injury and its potential mechanism, we employed bioinformatic analysis, neurological assessments, and western blot analysis, as well as triphenyl tetrazolium chloride, hematoxylin and eosin, Nissl, and immunofluorescence staining. We identified 103 differentially expressed genes induced by cerebral I/R, including 75 upregulated genes and 28 downregulated genes enriched for certain biological processes (involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Another study revealed that sevoflurane alleviated hepatic IRI in mice by reducing oxidative stress and inflammatory response via the miR 218 5p/GAB2/PI3 K/AKT pathway. 37 Zhao et al 38 stated that postconditioning with sevoflurane reduced cerebral IR-induced neurological deficits in rats by suppressing neuroinflammatory responses through inhibition of the TLR4/MyD88/TRAF6 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that sevoflurane alleviated hepatic IRI in mice by reducing oxidative stress and inflammatory response via the miR 218 5p/GAB2/PI3 K/AKT pathway. 37 Zhao et al 38 stated that postconditioning with sevoflurane reduced cerebral IR-induced neurological deficits in rats by suppressing neuroinflammatory responses through inhibition of the TLR4/MyD88/TRAF6 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Salvia miltiorrhiza mitigates cardiac dysfunction and inflammation in rats with heart failure by inhibiting the formation of the MD2/TLR4-MyD88 complex [67]. Additionally, Astragaloside IV, Xiang Lin pills, berberine, and fluoxetine can inhibit the TLR4/MyD88/NF-κB signals, thereby exerting the effects of acute myocardial infarction, colitis, and ischemia-reperfusion injury, and relieve postoperative cognitive dysfunction and neuroinflammation in elderly mice [67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Polyene phosphatidylcholine, a wellknown hepatoprotective drug, has also recently been found to act on the TLR2/MyD88 signaling pathway, inhibiting the binding of MyD88 and TLR, and activating the IκB kinase (IKK) complex to alleviate synovial inflammation [81].…”
Section: Drug Therapy Targeting Myd88mentioning
confidence: 99%